The Dynamics of Behavioral Responses During a Crisis - Corinna Hartung; Gregory F. Veramendi; Joachim Winter (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
This paper investigates the dynamics of behavioral changes during a crisis. We study this in the context of the first year of the Covid-19 pandemic, where behavioral responses were important in mitigating the costs of the pandemic. To identify behavioral responses to unanticipated and transient health risk shocks, we combine high-frequency cellphone mobility data with detailed incidence data in Germany. Using an event-study design on local outbreaks, we find that county-level mobility immediately and significantly decreased by about 2.5% in response to an outbreak independent of non-pharmaceutical interventions. We also find that the reproduction rate decreased by about 17% in response to a local outbreak. Both behavioral responses are quite persistent even after the relative health risk has dissipated. By the time of the second wave, the behavioral response to a second or third shock is small or negligible. Our results demonstrate the importance of (1) integrating behavioral persistence in models used to study behavior and policies that change behavior, (2) the effectiveness of policies that provide high-frequency localized information on health risks, and (3) the potential persistence of behavioral changes after the Covid-19 pandemic has passed.
Keywords: D90; H12; I12; I18; 330; dynamics; behavioral response; crisis; covid-19